A Role for Taok2 in Listeria monocytogenes Vacuolar Escape. (25th June 2020) - Quereda, Juan J; Morel, Camille; Lopez-Montero, Noelia; Ziveri, Jason; Rolland, Steven; Grenier, Théodore; Aulner, Nathalie; Danckaert, Anne; Charbit, Alain; Enninga, Jost; Cossart, Pascale; Pizarro-Cerdá, Javier
Abstract: The bacterial pathogen Listeria monocytogenes invades host cells, ruptures the internalization vacuole, and reaches the cytosol for replication. A high-content small interfering RNA (siRNA) microscopy screen allowed us to identify epithelial cell factors involved in L. monocytogenes vacuolar rupture, including the serine/threonine kinase Taok2. Kinase activity inhibition using a specific drug validated a role for Taok2 in favoring L. monocytogenes cytoplasmic access. Furthermore, we showed that Taok2 recruitment to L. monocytogenes vacuoles requires the presence of pore-forming toxin listeriolysin O. Overall, our study identified the first set of host factors modulating L. monocytogenes vacuolar rupture and cytoplasmic access in epithelial cells.